Critical Review of Criminalization Policies in Law Number 1 of 2023 Concerning the KUHP - Murshal Senjaya; Rusli Subrata (PT FORMOSA CENDEKIA GLOBAL, 2023)
The Criminalization Policy in Law Number 1 of 2023 concerning the Criminal Code is First, criminalization is limited to determining an act as a criminal offense which is punishable by criminal sanctions. Second, criminalization is a complex problem because there are different types of acts that can be criminalized, differences in values and norms in society. Third, important principles that need to be considered in criminalization are the principle of legality, the principle of subsidiarity, and the principle of equality before the law. Finally, the criteria to consider in criminalization include: The application of the Criminalization Policy in Law Number 1 of 2023 concerning the Criminal Code is an example of Article 509 of Law Number 1/2023 of the Criminal Code which is contrary to the 1945 Constitution and has no binding legal force. Because within the limits of reasonable reasoning, criminal error in Article 509 of the National Criminal Code is on the informant (client), not on the advocate. So it is not right for an advocate to be convicted because of a client's false statement. Article 509 of the National Criminal Code contradicts: Article 1 paragraph (3) of the 1945 Constitution which states: The State of Indonesia is a State of Law.